Pengaruh Penyelenggaraan dan Penggunaan Infformasi Akuntansi Terhadap Persepsi Pengusaha Kecil atas Informasi Akuntansi: Suatu Riset Eksperimen - MARGANI PINASTI (The Indonesian Journal of Accounting Research, 2013)
This research is aimed at examining the effect of carrying on and applying accounting information on small entrepreneurs' perception to the information. It is an experimental research and uses two-group posttest-only design. The subjects of this research are 46 small enterprises in Central Java Province and are drawn with purposive sampling technique.The research shows that carrying on and applying accounting information is empirically proved having an effect on the small entrepreneurs' perception to the information. The t-test result shows that (after experimentation) there is statistically a significant difference on the perception to the accounting information between subjects of experimental group and subjects of control group. The difference is solely due to the treatment in the form of giving stimulus of carrying on and applying accounting information, and is not influenced by the prior difference factor between two groups. This has been proved by equivalency test using ANOVA to the characteristic of two groups. The result of discriminatory analysis shows that the effect of carrying on and applying accounting information is stronger than that of individual characteristic difference of the subjects' perception to the accounting information